2017
DOI: 10.13189/ujm.2017.050404
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Structural/Content Career Plateaus on Job Involvement: Do Institutional/Occupational Intentions Matter?

Abstract: This study examined the potential moderating roles of career officer's institutional intention and occupational intention on the relationship between structural/content career plateaus and job involvement in Taiwanese career military officers. Empirical data were collected from 338 career officers who received full-time training at the National Defense University in Taiwan. The results showed that the perception of structural/content career plateaus were both negatively related to job involvement. Furthermore,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 26 publications
(26 reference statements)
1
3
0
Order By: Relevance
“…In addition, majority of them had between five to more than fifteen years of experience in this hospital without any changes in their positions or responsibilities and only one fifth of them become head nurses. This results in the same line with Hossain (2018) (5) , and Su et al (2017) (27) they found that job satisfaction was negatively correlated with career plateau perception due to high percent of head nurses weren't satisfied with their career advancement to meet their work goals Moreover, Ramlal (2017) (28) , Hurst (2017) (9) , Badiane, (2016) (29) , Lukosi (2015) (30) , Godshalk and Fender (2015) (31) , and Hee and Ok (2019) (32) they revealed that career plateau has a direct negative impact on nursing staff job satisfaction, motivation, and performance due to low levels of recognition, co-workers relation, job security, and their job rotation. In addition, Hassan et al (2020) (19) found no significant relation between professional plateau and staff satisfaction, while their results showed that staff with high levels of career plateau have low total career satisfaction.…”
Section: Correlation Between Nursing Staff Perception Regarding Caree...supporting
confidence: 90%
See 3 more Smart Citations
“…In addition, majority of them had between five to more than fifteen years of experience in this hospital without any changes in their positions or responsibilities and only one fifth of them become head nurses. This results in the same line with Hossain (2018) (5) , and Su et al (2017) (27) they found that job satisfaction was negatively correlated with career plateau perception due to high percent of head nurses weren't satisfied with their career advancement to meet their work goals Moreover, Ramlal (2017) (28) , Hurst (2017) (9) , Badiane, (2016) (29) , Lukosi (2015) (30) , Godshalk and Fender (2015) (31) , and Hee and Ok (2019) (32) they revealed that career plateau has a direct negative impact on nursing staff job satisfaction, motivation, and performance due to low levels of recognition, co-workers relation, job security, and their job rotation. In addition, Hassan et al (2020) (19) found no significant relation between professional plateau and staff satisfaction, while their results showed that staff with high levels of career plateau have low total career satisfaction.…”
Section: Correlation Between Nursing Staff Perception Regarding Caree...supporting
confidence: 90%
“…These results were supported by Lin et al (2020) (44) , Jiang (2016) (45) , and Lee and Herbst-Bergin (2014) (12) they revealed that high rate of nursing staff were experience professional plateau due to low opportunities of promotional and professional growth. In contrary Su et al (2017) (27) , and Brown-Wilson and Parry (2013) (46) they reported that although nursing staff were plateaued, their jobs provide them with valuable learning opportunities to be confident with their skills and competence.…”
Section: Levels Of Nursing Staff Perception Regarding Total Career Pl...mentioning
confidence: 94%
See 2 more Smart Citations